TRANSFORMATION OF PRODUCTION MANAGEMENT PRINCIPLES IN CRISISCONDITIONS - SKORUPSKYI, Kostiantyn (Herald of Khmelnytskyi National University. Economic sciences, 2025)
Modern conditions of functioning of production enterprises are characterized by high dynamics of changes, caused by globalization, development of technologies, instability of the market environment and crisis phenomena of economic, political and ecological nature. In such conditions, there is an urgent need to rethink traditional approaches to production management and to form new principles that will ensure its efficiency, flexibility and sustainability.The article is devoted to the generalization and systematization of approaches of Ukrainian and foreign scientists to the isolation of principles of production management, the justification of their own classification of these principles, as well as the analysis of the transformation of these principles in conditions of crisis.In the process of research, a set of methods of scientific knowledge was used, in particular, analysis and synthesis to systematize the approaches of foreign and Ukrainian scientists to the isolation of production management principles, the comparative analysis method to identify common and different aspects in the interpretation of strategic, technological, organizational, economic, social and environmental principles of production process management, the generalization method to substantiate the principles of production management in crisis conditions and formulate conclusions. The article provides a thorough analysis of the approaches to the isolation of production management principles proposed by Ukrainian and foreign scientists. The classification of production management principles according to strategic, technological, organizational, economic, social and environmental approaches is substantiated, which allows for a comprehensive assessment of the production process management system. The transformation of these principles in conditions of crisis phenomena, such as pandemics, military conflicts and economic recessions, is studied, which necessitates the need for flexible approaches to the management of production systems. Based on the analysis, updated principles of production management in crisis conditions are proposed, which contribute to increasing its stability, adaptability and efficiency.The results of the study confirmed that production management is a multidimensional process that combines strategic planning, technological development, organizational efficiency, economic feasibility, social responsibility and environmental sustainability. Changes in the main aspects of production management in crisis conditions demonstrate the need to adapt management strategies to new challenges. Enterprises are faced with the need to optimize costs, reduce operating cycles, increase the efficiency of resource use, digitize processes and strengthen anti-crisis management.
Keywords: production; management; principle; production management; operational management; principles of production management